Performance-based seismic bridge design for damage and loss limit states. - Mackie, K. R.
Recent efforts in the earthquake engineering community have focused largely on developing a performance-based earthquake engineering assessment methodology. However, equally important is applying such a methodology to the design of structures. Probabilistic performance-based seismic design enables design and acceptance criteria to be specified by a continuum of limit states and incorporates uncertainty in all the sources of data. This paper introduces a non-iterative method, based on the Pacific Earthquake Engineering Research Center framework, for design of bridge structures in terms of single or multiple physical design parameters, such as column height and diameter. Design parameter solutions are obtained from explicit consideration of uncertainty in the hazard, demand, damage, and loss to the structure by way of specifying a level of confidence in the resulting design under different performance objectives. Similar to other performance-based methodologies, performance objectives consist of a performance level and a hazard level. Design equations are derived for performance levels defined in terms of bridge damage and loss. Examples are presented of both univariate and bivariate design parameter cases for typical reinforced concrete highway overpass bridges in California.
Keywords: Performance-based earthquake engineering; Highway bridge; Repair cost ratio; Confidence level; Performance objective